(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Online banking offers a convenient electronic channel where customers can manage bank account and perform banking transaction over the internet. Online banking has many benefits but there are also risks involved. The internet is a wide area network of computer connected around the world to facilitate date transmission and exchange dul to the open nature of the internet all web based services are inherently subjects to risks such as online theft of user Id/user name, password, virus attacks, hacking and fraudulent transactions. Internet banking offers 24-hour access to customer accounts everyday it is a quick and anywhere, anytime and from any computer with access to the internet.